Cumulative effect of the plasma total homocysteine-related genetic variants on schizophrenia risk. (30th December 2016) - Kinoshita, Makoto; Numata, Shusuke; Tajima, Atsushi; Nishi, Akira; Muraki, Sho; Tsuchiya, Atsushi; Umehara, Hidehiro; Watanabe, Shin-ya; Imoto, Issei; Ohmori, Tetsuro
Abstract: Previous studies suggest that elevated total homocysteine levels and the methylenetetrahydrofolate reductase ( MTHFR) C677T polymorphism, which correlates with plasma total homocysteine levels, are risk factors for schizophrenia (SCZ). Recently, a large genome-wide association study (GWAS) of plasma total homocysteine levels in individuals of European ancestry identified many single-nucleotide polymorphisms (SNPs) ( n =13, 974). The primary purpose of this study was to examine the association between these plasma total homocysteine-related SNPs and SCZ in the Japanese population. First, we investigated associations between six SNPs and plasma total homocysteine levels in non-psychiatric subjects in the Japanese population ( n =1030). Then, we evaluated the cumulative effects of three SNPs on SCZ risk by calculating the Genotype Risk Score (GRS) (1120 cases, 2643 controls). Of the six SNPs examined, we replicated similar associations with the European GWAS at four loci ( CENPQ, CPS1, MTHFR, and MUT ). GRS based on three SNPs ( CENPQ, CPS1, and MTHFR ) was significantly associated with SCZ. Our findings suggest that common polygenic variations, which are associated with the plasma total homocysteine levels, may contribute to the risk of SCZ. Highlights: Significant associations at four loci with plasma total homocysteine. Significant association at MTHFR C677T with SCZ risk. No significant associations at other three loci with SCZ risk. Significant cumulative effect of the missense genetic variants on SCZ risk.